Stimulation of development of the rural areas: eurupean experience and ukrainian reality - Барановський, Микола (Human Geography Journal, 2016)
The European experience of reforming of the agrarian sector and rural territories is described, the reasonability of its usage to solve the problems of Ukrainian village is grounded, the evolution of the general agrarian policy in countries of the European Union during the 60s of the 20th – beginning of the 21st centuries is analyzed, the sense of the modern conceptions of Ukraine’s rural sector reforming is characterized, the reasons for low efficiency of mechanism of rural development support are defined, the possible sources of financing the measures stimulating the developments of problem rural territories of Ukraine are examined.